The impact of household air pollution from solid fuel use on rapid decline in kidney function and chronic kidney disease: A nationwide longitudinal cohort study - Wei-Zhen Tang; Wei-Ze Xu; Tai-Hang Liu; Qin-Yu Cai; Fei-Han; Ya-Ting Jia; Bo-Yuan Deng; Zhi-Yong Xiang; Yi Deng; Peng Guo; Jun Ding (The Journal of Nutrition, Health and Aging)
Background: The study investigates the link between indoor air pollution from non-clean fuels and kidney function decline, particularly in middle-aged and elderly individuals in China. Method: This prospective cohort study included 4,207 participants, with kidney function assessed through eGFR (using serum creatinine and cystatin C). Logistic regression models were used to examine the link between household solid fuel use and the risk of rapid kidney decline and CKD. Sensitivity analyses were also conducted using eGFR estimates based on creatinine or cystatin C alone. Results: Trend regression revealed that more frequent solid fuel use was associated with higher risks of both rapid kidney decline and CKD. Using solid fuels only for cooking was associated with a higher risk of CKD (OR 1.70; 95% CI: 1.07–2.70). Participants who switched from solid to clean fuels for cooking showed no significant changes in kidney function. Subgroup analysis revealed that women, individuals with lower education, non-smokers, non-drinkers, and those married or cohabiting had higher risks of rapid kidney decline and CKD with solid fuel use for heating. Similarly, those with lower education, non-smokers, and married/cohabiting individuals also had increased CKD risk with solid fuel use for cooking. Patients with gastrointestinal diseases had a significantly higher risk of rapid kidney function decline when using solid fuels for heating. Hypertensive patients had elevated risks of both rapid kidney decline and CKD with solid fuel use. Residents of concrete or steel multi-story buildings using solid fuels had the highest risks of rapid kidney decline and CKD. Those living in homes smaller than 120 square meters with solid fuel use also faced increased risks of kidney function decline. Conclusion: The results show a strong link between household air pollution and increased risk of kidney disesases. Improving household heating and cooking conditions could help prevent kidney damage.